Changes in job stability: evidence from lifetime job histories - Miikka Rokkanen; Roope Uusitalo (Institute for the Study of Labor (IZA), 2010)
We use lifetime job histories from the pension records to evaluate changes in job stability in Finland between 1963 and 2004. We specify a duration model and estimate the effects of elapsed duration, age, and calendar time on the hazard of job ending using individual-level panel data spanning over four decades. We find that this hazard increased during the recession years in the early 1990s but has now returned to the level that prevailed in the 1970s. We also demonstrate that the fluctuations in the hazard rate together with the changes in labor market entry rates have complicated dynamic effects on the tenure distribution, and that analysing the changes in job stability based on the elapsed duration of ongoing jobs may be quite misleading.
Keywords: J63; 330; Job stability; duration model; Arbeitsplatzsicherung; Betriebszugehörigkeit; Erwerbsverlauf; Statistische Bestandsanalyse; Schätzung; Finnland